Sistema web eficiente para la gestión administrativa en una empresa de transportes privada - Campos Montero, Brian (2024)
The current research was carried out with the purpose of improving the efficiency of maintenance, sales and human resources processes in a transportation company. To achieve this goal, a web application was developed integrating the Laravel 10 framework, the PHP 8.2.4 programming language and a MySQL 8.0.34 database. In addition, the Model-View-Controller approach was applied in order to reduce resource consumption and speed up navigation time. On the other hand, the agile SCRUM methodology was chosen to supervise the implementation, which facilitated team development, error correction and timely completion of activities within the estimated time. In addition, an economic feasibility study was carried out, the results of which indicated that the project is considered profitable and profitable. Likewise, software tests were performed in JMeter, yielding results of 6400, 1055 and 500 simultaneous users for the sales, maintenance and human resources subsystems, respectively. Finally, the total time dedicated to the development of the system was 39 days.